Presence and Characterization of a Novel cfr-Carrying Tn558 Transposon Derivative in Staphylococcus delphini Isolated From Retail Food - Zhang, Feng; Wu, Shi; Huang, Jiahui; Yang, Runshi; Zhang, Jumei; Lei, Tao; Dai, Jingsha; Ding, Yu; Xue, Liang; Wang, Juan; Chen, Moutong; Wu, Qingping (Frontiers in Microbiology, 2021)
Antimicrobial resistance has become a major public health threat. Food-related Staphylococcus species have received much attention due to their multidrug resistance. The cfr gene associated with multidrug resistance has been consistently detected in food-derived Staphylococcus species. In this retrospective study, we examined the prevalence of cfr-positive Staphylococcus strains isolated from poultry meat in different geographical areas of China from 2011 to 2016. Two cfr-positive Staphylococcus delphini strains were identified from poultry meat in China. Comparative and whole-genome analyses were performed to characterize the genetic features and overall antimicrobial resistance genes in the two S. delphini isolates 245-1 and 2794-1. Whole-genome sequencing showed that they both harbored a novel 20,258-bp cfr-carrying Tn558 transposon derivative on their chromosomes. The Tn558 derivative harbors multiple antimicrobial resistance genes, including the transferable multiresistance gene cfr, chloramphenicol resistance gene fexA, aminoglycoside resistance genes aacA-aphD and aadD, and bleomycin resistance gene ble. Surprisingly, within the Tn558 derivative, an active unconventional circularizable structure containing various resistance genes and a copy of a direct repeat sequence was identified by two-step PCR. Furthermore, core genome phylogenetic analysis revealed that the cfr-positive S. delphini strains were most closely related to S. delphini 14S03313-1 isolated from Japan in 2017 and 14S03319-1 isolated from Switzerland in 2017. This study is the first report of S. delphini harboring a novel cfr-carrying Tn558 derivative isolated from retail food. This finding raises further concerns regarding the potential threat to food safety and public health safety. The occurrence and dissemination of similar cfr-carrying transposons from diverse Staphylococcus species need further surveillance.